EXAMINING THE ROLE OF MILLET ENTREPRENEURIAL PRODUCTION IN IMPROVING FOOD SECURITY AND NUTRITION IN CHIVI RURAL DISTRICT - Mabhanda, Wilson; Sibanda, Khulekani (Jurnal Ekonomi dan Bisnis Airlangga, 2025)
Introduction: Existing research extensively documents food shortages, hunger, and poverty in Africa and Asia.  Climate change is a major driver of worsening food insecurity, contributing to these problems and negatively impacting a growing global population's health, nutrition, and economic well-being. Smallholder farmers face significant challenges in improving food security and nutrition through millet cultivation. This study examined the role of millet entrepreneurship production among 15 farmers, enhancing food security and nutrition in rural households within Zimbabwe’s Chivi District. Methods: Data were collected through in-depth face-to-face interviews and focus groups, using a descriptive qualitative case study design. To capture the diverse landscape of smallholder farmers in an informal context, both purposive and snowball sampling methods were utilized to select participants for the study. Results: According to the findings, millet entrepreneurship in the Chivi district has improved community households' food security and nutrition, demonstrating that small grain agriculture thrives in climatically challenging regions and raises living standards. Among the favorable benefits, rural farmers produce better food nutrition, have higher incomes, improved living conditions, and increased educational opportunities for their children. Conclusion and suggestion: The study concludes that, despite difficulties with labor-intensive farming and a lack of farming inputs, millet entrepreneurial production generally improved livelihoods. The study suggests that to optimize the results for livelihood, the Zimbabwean government's food security policy agenda should support smallholder rural farmers in their efforts to increase entrepreneurial millet production. Ultimately, smallholder farmers in dry regions are encouraged to adopt small grain cultivation due to its high yield potential despite climate change challenges.